REPRESENTASI MAKNA SIMBOL RAGAM HIAS PADA RUMAH LONTIOK KABUPATEN KAMPAR RIAU(Analisis Semiotika Roland Barthes Mengenai Makna Simbol Rumah Lontiok di Desa Ranah Air Tiris Kabupaten Kampar) - Putra, Wahyu Wananda; Yohana, Nova Yohana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
In general, traditional houses can be interpreted as a building that reflects a region in Indonesia which symbolizes the culture and characteristics of the local community. While traditional house tradiosional Bendang Riau Kampar District is also called the House Lontiok House (tapering) built in a long process involving the wider community and traditional ceremonies. Kampar, Bendang Traditional House is located in the village of Water Tiris aspect that has been aged for decades, this custom home also has an appeal of the art architecture that reflects the culture of the Malay Islamic Army with a very thick,. Home Lontiok House has a unique shape and its decoration and meaning of the symbols contained in it one of the decorative motif is in the form of bee motif Depending which have symbolic values contained in the Bendang Traditional house. Material processing, selection form, the use of decoration and meaning allegedly closely related to the value of Indigenous Peoples and social values. This phenomenon makes researchers interested in conducting research that aims to Know the Meaning of Denotation symbols contained Decorations On Traditional House Traditional Bendang, Know the Meaning connotation Decorations symbols contained in Traditional House Traditional Bendang, Knowing mythical symbols Decorations the Traditional Houses Bendang.This study uses Semiotics analysis is part of the form analilis different qualitative content with quantitative content analysis. Qualitative content analysis is focused on the content of the lines of communication. Qualitative content analysis in greater depth in a study. -Descriptive qualitative research approach to textual analysis using methods of structural analysis and commonly called semiotic connotations by Roland Barthess.Results from this study is that the decorative motifs carved on custom home Lontiok House Riau Kampar district has a message or meaning in accordance with the pattern of motifs carved decoration is also in line with the Bohemian everyday.Keywords: Symbol Meaning, Decorations Home Lontiok House, Representation